2022
DOI: 10.31004/edukatif.v4i3.2679
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Mathematic Education untuk Meningkatkan Aktivitas dan Hasil Belajar Matematika Siswa Sekolah Dasar

Abstract: Rendahnya hasil belajar siswa pada mata pelajaran matematika khususnya pada materi bangun ruang menjadi temuan observasi dilapangan. Banyaknya siswa yang kesulitan dalam menyelesaikan soal terkait dengan volume bangun ruang menjadi indikasi menjadi akar masalah rendahnya hasil belajar. Pendekatan Matematika Realistik menjadi salah satu solusi yang memungkinkan dapat mengatasi permasalahan yang ditemukan. Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika khususnya pada materi bangun ruang sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
0
0
2
Order By: Relevance
“…In this learning, students must be emotionally and orally active, which is the advantage of this model in increasing student learning activities. The study's findings using the CRH cooperative learning model demonstrate that science education activities at State Elementary School 21 Sawah Tangah for grade V students have increased, as seen through the graph in cycle I and cycle II, which reached a percentage of more than 80%(Safrizal et al, 2022).…”
mentioning
confidence: 79%
“…In this learning, students must be emotionally and orally active, which is the advantage of this model in increasing student learning activities. The study's findings using the CRH cooperative learning model demonstrate that science education activities at State Elementary School 21 Sawah Tangah for grade V students have increased, as seen through the graph in cycle I and cycle II, which reached a percentage of more than 80%(Safrizal et al, 2022).…”
mentioning
confidence: 79%
“…This is consistent with prior research, which found that mathematics learning, which should be provided with activities and active participation from students, is now exclusively offered by focusing on the teacher. Using suboptimal learning strategies and models leads to a saturated and monotonous mathematics learning process (Safrizal et al, 2022). Students should not simply accept what is handed to them, but also engage in critical thinking when solving mathematical problems.…”
Section: Students' Limited Ability To Grasp Basic Mathematical Conceptsmentioning
confidence: 99%
“…Mathematics is taught at all stages of education, including elementary school (SD), middle school (SMP), high school (SMA), and college (Fauzi et al, 2020). Mathematics study focuses on improving logical, analytical, systematic, critical, and creative thinking (Safrizal et al, 2022). In elementary school, the mathematics learning process will cover basic mathematical concepts and tools that will assist students with their arithmetic work at a higher level (Suparno, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kebijakan-kebijakan baru yang menyertai kurikulum ini, dirasa sulit karena masih minimnya pembekalan yang diterima guru, dan hal ini tentunya akan berakibat pada keberhasilan kurikulum merdeka dalam meningkatkan capaian belajar peserta didik. Proses pembelajaran yang demikian tidak efektif karena akan menimbulkan kurang berkembangnya kemampuan peserta didik dan hasil belajar yang dicapainya (Safrizal et al, 2022). Guru sebagai pihak yang terlibat langsung dalam penerapan kurikulum harus siap untuk menerapkan kurikulum merdeka.…”
Section: Pendahuluanunclassified